BELEŠKA 0 UTICAJU CENOVNE KONKURENTNOSTI NA KONVENCIONALNU TEORIJU I UKUPNU ISPLATIVOST INTRA-INDUSTRIJSKE TRGOVINE - Malović, Marko (Economic Annals, 2006)
Contrary to much of the mainstream literature on trade in tnonopolistic competition setting, we point out the importance of departure from CES dogma and consequently revealed, if thusfar neglected, price competitiveness effect, as a supplement to the classical Dixit-Stiglitz "love of variety” Quite apart from initial price and cost cuts due to greater competition as well as increased consumer welfare as a corollary of more substitutes being available for consumption, there is additional room for price-cost competitiveness boost in terms ofscale economies grasped by global market expansion of successful varieties (firms). Analyticalframework developed in the paper has led us to conclude that intraindustry trade does lower prices and enablegreater variety, in as much as it raises efficiency by melting thegap between the zero-profit equilibrium utility and the constrained optimum utility. However, unlike some most recent contributions, our supposition offurther downward flexibility of marginal costs prevents us from unambiguously claiming that national firms in the open economy must be fewer as opposed to the autarky case. Put differently, profit margins need not necessarily befallingpro rata (or at all,for that matter) with world prices. That might be one plausible explanation forjust why in spite ofevident pro- competitive effects within the EU-automobile industry, its price-cost wedges did notfall, but have rather reflated still.